LANGUAGE STRUCTURE: KEY DIFFERENCES BETWEEN ENGLISH AND UZBEK - Hasanova Sevinch Hotam qizi; Umarqulova Gulshoda Ibrohimovna; Toshboyeva Bibinur Komil qizi (TADQIQOTLAR, 2025)
Abstract This article presents a comprehensive contrastive analysis of the fundamental structural differences between English and Uzbek. It systematically explores divergences across phonological, morphological, and syntactic levels, highlighting how their distinct typological classifications lead to profoundly different grammatical and expressive systems. The analysis aims to provide insights for linguists, language educators, and learners by outlining the core challenges and unique features encountered when navigating these two distinct linguistic frameworks.